Students’ learning environment and attitudes toward science in light of the teach less, learn more initiative - Tan, Kim Choo Evelyn (Curtin University, 2011)
In light of the ‘Teach Less Learn More’ (TLLM) initiative, the thrust of which is to teach in such a way as to guide and facilitate students to seek out information on their own accord and inculcate in them the skills and habits of life-long learning, thus equipping them to be enterprising players of the knowledge-based economy of the 21st century, greater emphasis was placed on inquiry-based learning in science in the revised science curriculum in Singapore in 2008.As inquiry-based learning rests on the bedrock of the theory of constructivism, this research exercise was carried out to determine if there were differences between students’ preferred and the actual constructivist learning environment in the classrooms using both the Preferred and Actual Forms of the Constructivist Learning Environment Survey (CLES). The students’ perceptions of their teachers’ interpersonal behaviour were also mapped using the Questionnaire on Teacher Interaction (QTI) (Elementary). An attempt was made to determine if there were any associations between the constructivist learning environment and students’ attitude to science lessons, in terms of their enjoyment of science lessons. In addition, the associations, if any, between teachers’ interpersonal behaviour and students’ enjoyment of science lessons, were also examined. Information regarding the different programmes designed by schools to bring about greater engaged learning and to what extent the landscape of assessment had changed in view of the TLLM initiative was gathered using an investigator-designed survey form.Findings indicated that generally, there was a disparity between what the students would like to have and the existing level of constructivist classroom learning environment. The disparity was most significant in the scale of ‘Shared Control’. Regarding students’ perception of their teachers’ interpersonal behaviour, students perceived their teachers to display strong leadership in class, characterized by a helpful, friendly and understanding disposition but strict and stringent in giving students responsibility and freedom.No association was found between the constructivist learning environment and students’ enjoyment of science lessons. However, teachers’ behaviours like strong leadership, helpfulness, friendliness and understanding were positively correlated to the students’ enjoyment of their science lessons.Many schools had designed interesting activities to engage their students. However, assessment was still generally summative in nature. Though some schools tried to incorporate different types of alternative assessments, the general feeling was that different modes of alternative assessments seemed wanting at this point in time, with the age-old science practical test being the main form of performance-based assessment in all the schools surveyed.Findings arising from research of this nature provide teachers with information about the environment in which their students are immersed in every day for many hours. Being thus informed, teachers can take steps to rectify what is lacking and the outcome will be a classroom environment that is conducive and supportive of engaged learning.